A quantum dot / nanosheet doped coating reflective film and preparation method thereof

By growing quantum dots in situ on CTF-1 nanosheets, a quantum dot/nanosheet-doped reflective film was prepared, which solved the problems of poor dispersion and low stability of quantum dots, and achieved a reflective film with high brightness, uniform brightness and good mechanical properties.

CN118994691BActive Publication Date: 2025-04-01NINGBO CHANGYANG TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411480992.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-04-01
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Quantum dots have poor dispersion during actual use and are prone to form aggregates, resulting in a decrease in luminous efficiency and material stability.

Method used

The optical reflective film was prepared by growing quantum dots in situ on the CTF-1 nanosheets, and the quantum dot/nanosheet material with the [0D+2D] structure was prepared and added to the coating solution.

Benefits of technology

The brightness, brightness uniformity, wear resistance, scratch resistance and tensile strength of the reflective film are improved, and the problems of quantum dot agglomeration and material stability are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118994691B_ABST
    Figure CN118994691B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of reflective film, and provides a quantum dot / nanosheet doped coated reflective film and a preparation method thereof, wherein the preparation method comprises the steps of: using aromatic para-dinitrile as a monomer, dichloromethane as a solvent, and a strong acid as a catalyst, and polymerizing to obtain a stacked nanosheet; dispersing the nanosheet and a quantum dot precursor composition in a solvent, wherein the precursor composition comprises cadmium acetate, wherein the concentration of cadmium acetate is 0.12-0.2 mg / mL, and the mass ratio of the nanosheet to cadmium acetate is 7-10:1, and quantum dots are grown in situ on the nanosheet by a solvothermal method to obtain a quantum dot / nanosheet composition; and components including the quantum dot / nanosheet composition and polymer particles are divided into a coating liquid, and a reflective film is obtained by coating. In situ growth of quantum dots on the nanosheet, quantum dot agglomeration is alleviated, and a [0D+2D] composition is introduced into a coating to improve the brilliance, brightness uniformity, wear resistance, scratch resistance, and tensile strength of the reflective film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of reflective films, and in particular to a quantum dot / nanosheet doped coated reflective film and a preparation method thereof. Background Art

[0002] As a low-dimensional semiconductor material, quantum dots are generally composed of IV, II-VI, IV-VI or III-V elements, and their sizes in three dimensions are no more than twice the exciton Bohr radius of the corresponding semiconductor material. Quantum dot materials can control the luminescent color and purity by adjusting their own size, thereby achieving a wider color gamut coverage. Quantum dot materials have great development potential in the display field due to their advantages such as high color gamut, high brightness, and high color purity. Compared with traditional display technology, quantum dot display technology can make the screen present more vivid and realistic colors; produce higher brightness light, and maintain clear display effects in bright environments; the luminescent color is pure and the clarity is high, avoiding the problems of color mixing and poor uniformity in traditional display technology. For example, patent CN112444895A discloses a quantum dot reflective brightening film that can block cross light into unidirectional light and reuse the light through reflection to achieve a brightening effect.

[0003] However, due to the characteristics of high specific surface area and surface energy, quantum dots have poor dispersibility in actual use, and the particles are easily attracted to each other and easily form agglomerates. When the distance between quantum dots is less than its exciton Bohr radius, the material will undergo electron-hole recombination quenching, resulting in reduced luminous efficiency and blue shift of luminescent peak. In addition, quantum dots are also susceptible to environmental factors such as temperature, humidity, and light, which leads to decreased material stability, and irreversible reactions may occur, resulting in performance degradation. The dispersibility of quantum dots can be improved by introducing functional groups for surface modification, reducing the attraction between particles, and increasing the barrier or repulsion between particles, thereby improving the dispersibility of quantum dots. The stability of quantum dots can be improved by coating the surface with silicon shells and polymers to form an isolation layer to prevent quantum dots from directly contacting the external environment, thereby improving their stability. However, the method for modifying the material after synthesis is complicated, difficult to process, poor stability of the finished product, and low yield. Therefore, an ideal solution is needed. Summary of the invention

[0004] The present invention provides a quantum dot / nanosheet doped coating reflective film and a preparation method thereof, wherein quantum dots are grown in situ on CTF-1 nanosheets to prepare a quantum dot / nanosheet material having a [0D+2D] structure, and the quantum dot / nanosheet material is added to a coating liquid to prepare an optical reflective film. The in-situ growth method can alleviate the problem of mutual attraction and agglomeration between quantum dots, and the introduction of the [0D+2D] composition into the coating can improve the brightness, brightness uniformity, wear resistance, scratch resistance and tensile strength of the reflective film.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a quantum dot / nanosheet doped coated reflective film comprises the following steps:

[0007] 1) Using aromatic para-dinitrile as monomer, dichloromethane as solvent and strong acid as catalyst, stacked nanosheets CTF-1 are obtained through polymerization reaction;

[0008] 2) dispersing the nanosheet and quantum dot precursor composition in a solvent, wherein the precursor composition includes cadmium acetate, the concentration of cadmium acetate is 0.12-0.2 mg / mL, the mass ratio of nanosheet to cadmium acetate is 7-10:1, and in-situ growing quantum dots on the nanosheet by a solvothermal method to obtain a quantum dot / nanosheet composition;

[0009] 3) The components including the quantum dot / nanosheet composition and the polymer particles are prepared into a coating liquid, and the coating is performed to obtain a reflective film.

[0010] Preferably, in step 1), the aromatic para-dinitrile is selected from at least one of terephthalonitrile and 2,5-dimethylterephthalonitrile, and terephthalonitrile is more preferred. The monomer concentration is 8-12 mg / mL.

[0011] Preferably, the strong acid in step 1) is selected from at least one of trifluoromethanesulfonic acid, concentrated sulfuric acid and trifluoroacetic acid, and trifluoromethanesulfonic acid is further preferred. The amount of catalyst required for the polymerization reaction is 0.3-1 mL per 100 mg of monomer.

[0012] Preferably, the polymerization reaction in step 1) is carried out at 80-110° C. for 4-8 hours, more preferably at 100° C. for 6 hours.

[0013] Preferably, after the polymerization reaction in step 1) is completed, the solution is quenched with ethanol; filtered, the product is washed alternately with CH2Cl2, DMF and ethanol solution, and dried in a vacuum oven; and then ultrasonically exfoliated to obtain nanosheets CTF-1.

[0014] Preferably, the precursor composition in step 2) further includes at least one of CdS, CdTe and CdSe, and more preferably CdSe.

[0015] Preferably, the mass proportion of cadmium acetate in the precursor composition is 50-70%.

[0016] Preferably, the solvent in step 2) is selected from at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), and chloroform, preferably DMF.

[0017] Preferably, the reaction conditions of the solvothermal method in step 2) are 170-190° C. for 5-7 hours.

[0018] Preferably, after the reaction in step 2) is completed, the temperature is lowered, the mixture is filtered, washed with ethanol and acetone for multiple times, and dried to obtain a quantum dot / nanosheet composition.

[0019] Preferably, the mass percentage composition of the coating solution in step 3) is:

[0020] Quantum dot / nanosheet composition: 2-8 wt%;

[0021] Polymer particles: 2-8 wt%;

[0022] Adhesive: 30-40 wt%;

[0023] Curing agent: 3-6 wt%;

[0024] Solvent: Balance.

[0025] Preferably, the polymer particles are selected from at least one of polymethyl methacrylate (PMMA), polybutyl methacrylate (PBMA), polyamide (PA), and polyurethane (PU), with a particle size of 3-5 μm and a spherical or ellipsoidal shape; the adhesive is selected from at least one of acrylic resin adhesive, polycarbonate resin adhesive, polyurethane resin adhesive, and polyimide resin adhesive, preferably acrylic resin adhesive; the curing agent is selected from at least one of isocyanate, epoxy resin, methyl phenolic resin, and dicyandiamide, preferably isocyanate curing agent; the solvent includes at least one group of DMF and ethyl acetate, DMF and butyl acetate, and DMF and butyl benzoate.

[0026] Preferably, in step 3), the coating liquid is coated on the surface of the reflective substrate, and heated and cured in an oven at 100-120° C. for 1-3 min to form a coating on the surface of the reflective substrate to obtain a quantum dot / nanosheet doped coated reflective film.

[0027] Preferably, the reflective substrate is selected from at least one of PET polyester film and PP polypropylene film, and more preferably PET polyester film.

[0028] The present invention also provides a quantum dot / nanosheet doped coated reflective film, which is prepared by the above preparation method.

[0029] Therefore, the beneficial effects of the present invention are as follows: (1) CTFs, as an organic framework material, has a rich triazine skeleton structure in both the plane and stacking directions. Its large surface area gives the material rich adsorption and catalytic active sites, which enables it to adsorb the precursor of quantum dots and grow quantum dots in situ through solvothermal reaction, so that the quantum dots are evenly dispersed on the nanosheets to avoid the agglomeration of quantum dots. The QDs / CTF-1 composition proposed in this patent can control the growth of quantum dots and further control the formation of agglomerates by adjusting the reaction time and the concentration of the precursor. Moreover, the one-pot method has simple steps, is easy to operate, and is suitable for large-scale production.

[0030] (2) This patent introduces quantum dots into the reflective film coating, and utilizes the advantages of quantum dot materials in quantum yield, spectral purity, and quantum size to improve the brightness and brightness uniformity of the reflective film. Among them, the luminescence band of cadmium selenide is within the appropriate visible light range and is more suitable for the field of display technology. At the same time, the thermosetting glue system can make the quantum dots have a certain isolation performance, and through the curing process, a high-strength, high-density barrier film is formed to play a role in moisture and oxidation resistance.

[0031] (3) Two-dimensional nanosheets have atomic-layer thickness and planar nanostructures. This ultra-thin structure enables them to exhibit unique properties in multiple dimensions. This patent adds CTF-1 nanosheets to the reflective film coating, and utilizes CTF-1's unique two-dimensional structure and highly ordered arrangement structure to enable it to effectively intercalate with polymer particles, thereby improving the dispersion uniformity of the coating particles and further improving the scratch performance of the reflective film coating. CTF-1 is self-polymerized by cyanide, and since there is no reversible dehydration process in the polymerization reaction, it has excellent chemical stability and thermal stability. At the same time, the rigid structure of CTF-1 exhibits excellent mechanical properties, so adding it to the coating can improve the tensile strength of the reflective film, giving the reflective film high strength and high toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of a quantum dot / nanosheet doped coated reflective film. In the figure: 1. [0D+2D] coating, 2. reflective substrate, 3. QDs / CTF-1, 4. polymer particles.

[0033] Figure 2 Schematic diagram of the structure of QDs / CTF-1. In the figure: 31, quantum dots, 32, CTF-1 nanosheets.

[0034] Figure 3 This is the chemical structure of CTF-1. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below through specific embodiments.

[0036] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are by weight, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.

[0037] Overall embodiment:

[0038] A method for preparing a quantum dot / nanosheet doped coated reflective film comprises the following steps:

[0039] Step 1: Preparation of nanosheet CTF-1 by microinterface method

[0040] (1) adding the monomer aromatic para-dinitrile terephthalonitrile or 2,5-dimethylterephthalonitrile to a solvent CH2Cl2, and dispersing by ultrasonication to obtain a monomer solution with a concentration of 8-12 mg / mL;

[0041] (2) Add a catalyst strong acid into a three-necked flask, the strong acid is selected from at least one of trifluoromethanesulfonic acid, concentrated sulfuric acid, and trifluoroacetic acid, and trifluoromethanesulfonic acid is more preferred. The amount of catalyst required for the polymerization reaction of every 100 mg of monomer is 0.3-1 mL; a device equipped with magnetic stirring and condensation reflux is used to uniformly drop the monomer solution into the upper device system, and react at 80-110°C for 4-8 hours, and more preferably at 100°C for 6 hours;

[0042] (3) After the polymerization reaction is completed, the solution is quenched with ethanol, filtered, and the product is washed alternately with CH2Cl2, DMF, and ethanol solutions, and dried in a vacuum oven to obtain stacked nanosheets, which are recorded as CTF-1.

[0043] CTFs stands for Covalent Triazine Frameworks, which are covalent triazine frameworks. CTF-1 is one of the CTFs, with the structural formula Figure 3As shown. CTF-1 nanosheets are polymerized through cyclotrimerization. Due to the presence of incompatible microinterfaces of CH2Cl2 and CF3SO3H in the reaction system, the resulting product has a stacked layer structure. The CTF-1 porous framework structure is a periodic network organic unit with the advantages of high porosity, large specific surface area, and good thermochemical stability. The CTF-1 triazine planar skeleton contains rich aromatic nitrogen structures, which can capture a large number of quantum dot precursors to provide nucleation sites for crystal growth, thereby obtaining quantum dots that grow uniformly on CTF-1 nanosheets and avoiding the formation of quantum dots agglomerates.

[0044] Step 2: Preparation of quantum dot / nanosheet composite QDs / CTF-1 by solvent thermal synthesis

[0045] (1) placing the CTF-1 powder prepared in step 1 and a solvent (selected from DMF, DMAC, and chloroform) in a blue-mouth bottle, stirring and dispersing, and ultrasonically exfoliating to obtain a CTF-1 nanosheet dispersion;

[0046] (2) Add the first precursor of quantum dots Cd(CH3CO2)2 and the second precursor to the dispersion of step (1), disperse by ultrasonication, and then add them to a stainless steel reactor lined with polytetrafluoroethylene. Heat the reaction system to 170-190 °C and maintain for 5-7 hours. After the reaction, cool the reactor, filter, wash with ethanol and acetone several times, and dry to obtain a quantum dot / nanosheet composite, recorded as QDs / CTF-1 (depending on the second precursor, CdS / CTF-1, CdTe / CTF-1 or CdSe / CTF-1 is obtained);

[0047] The concentration of the first precursor is 0.12-0.2 g / L; the mass ratio of CTF-1 to the first precursor is 7-9:1. Too little Cd(CH3CO2)2 content of the first precursor will lead to insufficient nucleation reaction of quantum dots, and too much Cd(CH3CO2)2 content of the first precursor will lead to agglomeration of quantum dots. The second precursor is selected from at least one of sulfur powder, tellurium powder, and selenium powder, preferably selenium powder. The mass ratio of the first precursor to the second precursor is 1-2:1;

[0048] The quantum dots include at least one of CdS, CdTe, and CdSe, preferably CdSe. The luminescence range of CdSe is within the wavelength range of visible light to the human eye. Therefore, CdSe quantum dots have the best effect in the display field due to their advantages such as suitable luminescence band, narrow emission bandwidth, and high light stability.

[0049] The schematic diagram of the structure of the QDs / CTF-1 composite is shown in Figure 2Quantum dots were grown in situ on CTF-1 nanosheets to prepare quantum dot / nanosheet materials with a [0D+2D] structure, where 0D represents zero-dimensional quantum dots (0D QDs) and 2D represents two-dimensional covalent triazine framework materials (2D CTF-1). The in situ growth method can alleviate the problem of mutual attraction and agglomeration between quantum dots.

[0050] Step 3: Apply reflective film

[0051] (1) dispersing a QDs / CTF-1 composition (at least one of CdS / CTF-1, CdTe / CTF-1, and CdSe / CTF-1, preferably CdSe / CTF-1) in a DMF solvent, dispersing by ultrasonication, and stirring to obtain a first suspension;

[0052] (2) dispersing the polymer particles, the adhesive, the curing agent, and the first suspension in the solvent in sequence, and stirring them evenly to obtain a coating liquid;

[0053] The polymer particles include at least one of polymethyl methacrylate (PMMA), polybutyl methacrylate (PBMA), polyamide (PA), and polyurethane (PU), with a particle size of 3-5 μm and a spherical or ellipsoidal shape; the adhesive includes at least one of acrylic resin adhesive, polycarbonate resin adhesive, polyurethane resin adhesive, and polyimide resin adhesive, preferably acrylic resin adhesive; the curing agent includes at least one of isocyanate, epoxy resin, methylphenolic resin, and dicyandiamide, preferably isocyanate curing agent; the solvent includes at least one of N,N-dimethylformamide (DMF) and ethyl acetate, DMF and butyl acetate, and DMF and butyl benzoate;

[0054] The composition and mass percentage of the coating liquid are as follows:

[0055] Quantum dot / nanosheet composition: 2-8 wt%;

[0056] Polymer particles: 2-8 wt%;

[0057] Adhesive: 30-40 wt%;

[0058] Curing agent: 3-6 wt%;

[0059] Solvent: balance;

[0060] (3) The obtained coating liquid is coated on the surface of the reflective substrate PET polyester film, and heated and cured in an oven at 100-120 °C for 1-3 min to form a coating on the surface of the reflective substrate, which is recorded as [0D+2D] coating, where 0D represents zero-dimensional quantum dots (0D QDs) and 2D represents two-dimensional covalent triazine framework material (2D CTF-1). A quantum dot / nanosheet doped coated reflective film is obtained.

[0061] The present invention also provides a quantum dot / nanosheet doped coating reflective film prepared by the above method, such as Figure 1 As shown, it is composed of a reflective substrate 2 and a [0D+2D] coating 1 coated on the surface thereof, and QDs / CTF-1 3 and polymer particles 4 are uniformly dispersed in the [0D+2D] coating 1. Figure 2 As shown, in QDs / CTF-1 3, quantum dots 31 are uniformly dispersed on the CTF-1 nanosheets. Embodiment 1:

[0062] A method for preparing a quantum dot / nanosheet doped coated reflective film, comprising the following steps:

[0063] Step 1: Synthesis of CTF-1 nanosheets

[0064] Dissolve 400 mg of terephthalonitrile in 40 mL of CH2Cl2 and disperse by ultrasonication to obtain a monomer solution. Add 2 mL of catalyst CF3SO3H into a three-necked flask, equipped with a magnetic stirring and condensation reflux device, and evenly drop the monomer solution into the upper device system, and react at 100 °C for 6 hours. After the polymerization reaction is completed, quench the solution with ethanol. Filter, wash the product alternately with CH2Cl2, DMF, and ethanol solution, and dry it in a vacuum oven for 12 hours to obtain stacked nanosheets CTF-1.

[0065] Step 2: Synthesis of CdSe / CTF-1 Composite

[0066] (1) Place 100 mg of CTF-1 powder and 100 mL of DMF in a blue-mouth bottle, stir at 80 °C for 3 hours, and perform ultrasonic exfoliation for 1 hour to obtain a CTF-1 nanosheet dispersion.

[0067] (2) 12.5 mg of Cd(CH3CO2)2 and 7.5 mg of selenium powder were placed in the above dispersion, ultrasonically dispersed for 3 h, and added to a stainless steel reactor lined with polytetrafluoroethylene. The reaction system was heated to 180 °C and maintained for 6 h. After the reaction, the reactor was cooled, filtered, washed with ethanol and acetone several times, and dried at 60 °C for 12 h to obtain a QDs / CTF-1 composite.

[0068] Step 3: Preparation of quantum dot / organic nanosheet doped reflective coating film

[0069] (1) Disperse 5 parts of CdSe / CTF-1 composition by weight into 20 parts of DMF solvent, perform ultrasonic dispersion for 1 hour, and stir to obtain a first suspension. Disperse 5.2 parts of methyl methacrylate particles, 38 parts of acrylic resin adhesive, 3.8 parts of isocyanate curing agent, and the first suspension into 28 parts of ethyl acetate in sequence, and stir to obtain a final coating solution.

[0070] (2) The obtained coating liquid is coated on the surface of a PET reflective substrate, and heated in an oven at 110°C for 2 minutes to form a [0D+2D] coating, thereby obtaining a quantum dot / organic nanosheet doped coated reflective film. Embodiment 2:

[0071] The difference from Example 1 is that the selenium powder in step 2 (2) is replaced by sulfur powder, and the QDs / CTF-1 composition is CdS / CTF-1. Embodiment 3:

[0072] The difference from Example 1 is that the selenium powder in step 2 (2) is replaced by tellurium powder, and the QDs / CTF-1 composition is CdTe / CTF-1. Embodiment 4:

[0073] The difference from Example 1 is that the amount of CTF-1 powder used in step 2 (1) is 120 mg. Embodiment 5:

[0074] The difference from Example 1 is that the reaction time of step 2 (2) is 9 hours. Embodiment 6:

[0075] The difference from Example 1 is that the reaction time of step 2 (2) is 4 hours.

[0076] Comparative Example 1:

[0077] The difference from Example 1 is that no CdSe / CTF-1 composition is added to the coating solution. Specifically:

[0078] A method for preparing a reflective film, comprising the following steps:

[0079] (1) By weight, 5.2 parts of methyl methacrylate particles, 38 parts of acrylic resin adhesive, and 3.8 parts of isocyanate curing agent are dispersed in 28 parts of ethyl acetate in sequence, and stirred to obtain a final coating solution.

[0080] (2) The obtained coating liquid is coated on the surface of the PET reflective substrate, and heated in an oven at 110° C. for 2 minutes to form a coating.

[0081] Comparative Example 2:

[0082] The difference from Example 1 is that commercially available CdSe quantum dots are directly added to the coating liquid. Specifically:

[0083] A method for preparing a reflective film, comprising the following steps:

[0084] (1) Disperse 5 parts of commercially available CdSe quantum dots in 20 parts of DMF solvent by weight, perform ultrasonic dispersion for 1 hour, and stir to obtain a first suspension. Disperse 5.2 parts of methyl methacrylate particles, 38 parts of acrylic resin adhesive, 3.8 parts of isocyanate curing agent, and the first suspension in 28 parts of ethyl acetate in sequence, and stir to obtain a final coating solution.

[0085] (2) The obtained coating liquid is coated on the surface of the PET reflective substrate, and heated in an oven at 110° C. for 2 minutes to form a coating.

[0086] Comparative Example 3:

[0087] The difference from Example 1 is that only CTF-1 is added to the coating liquid. Specifically:

[0088] A method for preparing a quantum dot / nanosheet doped coated reflective film, comprising the following steps:

[0089] Step 1: Synthesis of CTF-1 nanosheets

[0090] Dissolve 400 mg of terephthalonitrile in 40 mL of CH2Cl2 and disperse by ultrasonic to obtain a monomer solution. Add 2 mL of CF3SO3H into a three-necked flask equipped with a magnetic stirring and condensation reflux device, and evenly drop the monomer solution into the upper device system, and react at 100°C for 6 hours. After the polymerization reaction is completed, quench the solution with ethanol. Filter, wash the product alternately with CH2Cl2, DMF, and ethanol solution, and dry it in a vacuum oven for 12 hours to obtain CTF-1.

[0091] Step 2: Preparation of quantum dot / organic nanosheet doped reflective coating film

[0092] (1) Disperse 5 parts of CTF-1 by weight into 20 parts of DMF solvent, perform ultrasonic dispersion for 1 hour, and stir to obtain a first suspension. Disperse 5.2 parts of methyl methacrylate particles, 38 parts of acrylic resin adhesive, 3.8 parts of isocyanate curing agent, and the first suspension into 28 parts of ethyl acetate in sequence, and stir to obtain a final coating solution.

[0093] (2) The obtained coating liquid was coated on the surface of the PET reflective substrate and heated in an oven at 110°C for 2 minutes to form a [0D+2D] coating.

[0094] Comparative Example 4:

[0095] The difference from Example 1 is that CTF-1 powder and commercially available CdSe quantum dots are added to the coating liquid. Specifically:

[0096] A method for preparing a quantum dot / nanosheet doped coated reflective film, comprising the following steps:

[0097] Step 1: Synthesis of CTF-1 nanosheets

[0098] Dissolve 400 mg of terephthalonitrile in 40 mL of CH2Cl2 and disperse by ultrasonic to obtain a monomer solution. Add 2 mL of CF3SO3H into a three-necked flask equipped with a magnetic stirring and condensation reflux device, and evenly drop the monomer solution into the upper device system, and react at 100°C for 6 hours. After the polymerization reaction is completed, quench the solution with ethanol. Filter, wash the product alternately with CH2Cl2, DMF, and ethanol solution, and dry it in a vacuum oven for 12 hours to obtain CTF-1.

[0099] Step 2: CdSe and CTF-1 mixture

[0100] (1) Place 100 mg of CTF-1 powder and 100 mL of DMF in a blue-mouth bottle, stir at 80 °C for 3 hours, and ultrasonically treat for 1 hour to obtain a CTF-1 nanosheet dispersion.

[0101] (2) 12.5 mg of commercially available CdSe quantum dots were placed in the above dispersion, ultrasonically dispersed for 3 h, and added to a stainless steel reactor lined with polytetrafluoroethylene. The reaction system was heated to 180 °C and maintained for 6 h. After the reaction was completed, the reactor was cooled, filtered, washed with ethanol and acetone several times, and dried at 60 °C for 12 h to obtain a mixture of QDs and CTF-1.

[0102] Step 3: Preparation of quantum dot / organic nanosheet doped reflective coating film

[0103] (1) Disperse 5 parts of the mixture of QDs and CTF-1 into 20 parts of DMF solvent by weight, ultrasonically disperse for 1 hour, and stir to obtain a first suspension. Disperse 5.2 parts of methyl methacrylate particles, 38 parts of acrylic resin adhesive, 3.8 parts of isocyanate curing agent, and the first suspension into 28 parts of ethyl acetate in sequence, and stir to obtain a final coating solution.

[0104] (2) The obtained coating liquid is coated on the surface of the PET reflective substrate, and heated in an oven at 110° C. for 2 minutes to form a coating.

[0105] Comparative Example 5:

[0106] The difference from Example 1 is that the amount of CTF-1 powder used in step 2 (1) is 80 mg, resulting in a mass ratio of CTF-1 to the first precursor Cd(CH3CO2)2 of 6.4:1, which is lower than the preferred range of 7-10:1.

[0107] Comparative Example 6:

[0108] The difference from Example 1 is that in step 2 (2), the Cd(CH3CO2)2 content is 16.5 mg, and the selenium powder content is 9.9 mg. The mass ratio of CTF-1 to the first precursor Cd(CH3CO2)2 is 6:1, which is lower than the preferred range of 7-10:1.

[0109] Comparative Example 7:

[0110] The difference from Example 1 is that in step 2 (2), the Cd(CH3CO2)2 content is 10 mg and the selenium powder content is 6 mg. The concentration of Cd(CH3CO2)2 is 0.1 mg / mL, which is lower than the preferred range of 0.12-0.2 mg / mL.

[0111] Comparative Example 8:

[0112] The difference from Example 1 is that the catalyst used in step 1 is acetic acid.

[0113] Performance Test:

[0114] The performance of the reflective films prepared in each embodiment and comparative example was tested by the following method:

[0115] (1) Scratch test. Take a 20*20 mm reflective film and stick it on the sample table of the steel wool friction resistance tester. With a 200g weight, rub the coating surface of the reflective film back and forth against the light guide plate. Repeat 50 cycles at a speed of 12 mm / s. Then use a USB digital microscope to observe and compare the light guide plate area before and after friction. No obvious scratches are excellent, 1-5 scratches are good, and more than 6 scratches are poor.

[0116] (2) Agglomeration test: The QDs / CTF-1 composition was dispersed in a solvent, ultrasonically dispersed, and the suspension was dripped onto a copper grid. TEM was used to observe whether the quantum dots were aggregated.

[0117] The results are shown in the following table.

[0118] Table 1. Test results of reflective film performance

[0119]

[0120] From the table above:

[0121] (1) According to the results of Examples 1-3 and Comparative Examples 1 and 3, different quantum dots (CdSe, CdS, CdTe) grown in situ on CTF-1 nanosheets can improve the brightness and brightness uniformity of the reflective film, and CTF-1 can improve the scratch resistance of the coating and the tensile strength of the reflective film. Among them, CdSe / CTF-1 has the most obvious improvement on the performance of the reflective film.

[0122] (2) According to the results of Example 1, Example 4 and Comparative Example 5, the ratio of quantum dots to CTF-1 is also very critical. A high ratio of CTF-1 will result in a low ratio of quantum dots in QDs / CTF-1, and the brightness improvement of the resulting reflective film will be reduced; a low ratio of CTF-1 will result in a high ratio of quantum dots in QDs / CTF-1, and the quantum dots will easily agglomerate, resulting in poor brightness uniformity of the resulting reflective film.

[0123] (3) According to the results of Example 1 and Comparative Examples 2 and 4, CTF-1 is critical for the in-situ growth of quantum dots. Adding quantum dots directly to the coating solution or adding quantum dots to the CTF-1 dispersion will cause the quantum dots to form agglomerates, affecting the brightness uniformity of the reflective film.

[0124] (4) According to the results of Example 1, Example 5 and Example 6, the reaction time has an effect on the size, distribution and fluorescence intensity of quantum dots. As the reaction time increases, smaller quantum dots will continue to grow and the size of the quantum dots will gradually increase. At the same time, the growth rate of larger quantum dots is relatively slow, making the size distribution more concentrated. However, too long a time will lead to an increase in surface defects of quantum dots, thereby reducing the fluorescence intensity. Insufficient reaction time will result in uneven particle size of quantum dots and the fluorescence intensity will not reach the maximum value.

[0125] (5) According to the results of Example 1 and Comparative Example 7, the precursor concentration has an important influence on the growth process of quantum dots. A low precursor concentration will lead to uneven size distribution of quantum dots and insufficient fluorescence intensity. However, as the precursor concentration increases, the agglomeration of quantum dots may become more and more serious. Therefore, a moderate concentration can obtain a sample with good dispersion and uniform particle size distribution.

[0126] (6) According to the results of Example 1 and Comparative Example 8, when preparing nanosheets, the use of acetic acid as a catalyst will result in the size of the generated nanosheets being smaller, and even granular CTF-1 will appear, resulting in uneven dispersion of quantum dots on CTF-1 and agglomeration. At the same time, the reduction in the size of CTF-1 nanosheets will also lead to poor uniformity in the dispersion of polymer particles, which will ultimately result in a decrease in the scratch resistance and tensile strength of the coated reflective film.

[0127] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a quantum dot / nanosheet doped coating reflective film, characterized in that: Includes steps: 1) using aromatic para-dinitrile as monomer, dichloromethane as solvent and strong acid as catalyst, polymerizing to obtain stacked nanosheets; 2) a nanosheet and a quantum dot precursor composition are dispersed in a solvent, the precursor composition comprising cadmium acetate and a second precursor in a mass ratio of 1-2:1, the cadmium acetate concentration is 0.12-0.2 mg / mL, the second precursor is selected from sulfur powder, tellurium powder, and selenium powder, the mass ratio of the nanosheet to the cadmium acetate is 7-10:1, and quantum dots are in situ grown on the nanosheet by a solvothermal method to obtain a quantum dot / nanosheet composition; 3) A coating liquid is prepared and applied to obtain a reflective film; the coating liquid has the following mass percentage compositions: 2-8% quantum dot / nanosheet composition; 2-8% polymer particles; 30-40% adhesive; 3-6% curing agent; and the remainder is solvent.

2. The method for preparing a quantum dot / nanosheet doped coating reflective film according to claim 1, characterized in that: Step 1) The strong acid is selected from at least one of trifluoromethanesulfonic acid, concentrated sulfuric acid and trifluoroacetic acid.

3. The method for preparing a quantum dot / nanosheet doped coating reflective film according to claim 1 or 2, characterized in that: The polymerization reaction conditions of step 1) are 80-110° C. for 4-8 hours.

4. The method for preparing a quantum dot / nanosheet doped coating reflective film according to claim 1, characterized in that: The solvent in step 2) is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and chloroform.

5. The method for preparing a quantum dot / nanosheet doped coating reflective film according to claim 1 or 4, characterized in that: Step 2) The reaction conditions of the solvothermal method are 170-190° C. for 5-7 hours.

6. The method for preparing a quantum dot / nanosheet doped coating reflective film according to claim 1, characterized in that: The polymer particles are selected from at least one of polymethyl methacrylate, polybutyl methacrylate, polyamide and polyurethane.

7. The method for preparing a quantum dot / nanosheet doped coating reflective film according to claim 1, characterized in that: The adhesive is selected from at least one of acrylic resin adhesive, polycarbonate resin adhesive, polyurethane resin adhesive, and polyimide resin adhesive.

8. The method for preparing a quantum dot / nanosheet doped coating reflective film according to claim 1, characterized in that: The curing agent is selected from at least one of isocyanate, epoxy resin, methylphenolic resin and dicyandiamide.

9. The method for preparing a quantum dot / nanosheet doped coating reflective film according to claim 1 or 6 or 7 or 8, characterized in that: Step 3) coating the coating liquid on the surface of the reflective substrate, and heating and curing it in an oven at 100-120° C. for 1-3 min to form a coating on the surface of the reflective substrate to obtain a quantum dot / nanosheet doped coated reflective film.

10. The coated reflective film obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The substrate of the reflective film is polyester film or polypropylene film.

Citation Information

Patent Citations

  • High-insulation and high-thermal-conductivity polymer-based composite film material as well as preparation method and application thereof

    CN118027647A

  • KR20190008072A